WAVE PHYSICS IN THE DEVELOPMENT OF WIRELESS NETWORKS AND DATA COMMUNICATION - Putri Abdul, Aisyah Ramadhani; Muhammad Faiz Abar; Mahdy Zahy Silalahi; Adelyna Oktavia Nasution (Cattleya Darmaya Fortuna, 2025)
The rapid advancement of digital technology has emphasized the critical role of data communication in enhancing organizational efficiency and connectivity. At the heart of this transformation lies the fundamental principles of wave physics, particularly electromagnetic and optical waves, which serve as the backbone for both wired and wireless communication networks. This study explores the theoretical foundation and practical application of wave physics in modern networking technologies such as Wi-Fi, fiber optics, and 5G systems. Utilizing a descriptive qualitative approach through literature review, the research identifies how characteristics such as frequency, wavelength, and propagation behavior directly influence data transmission performance. Key findings indicate that the effective implementation of electromagnetic wave-based communication relies not only on technological innovation, such as beamforming and MIMO, but also on an in-depth understanding of environmental influences and wave behavior. Ultimately, this study underscores the indispensable role of wave physics in the continuous evolution of digital communication infrastructure.